The internest. (Economist, 2004)
Honeybees want to make honey, while internet host providers want to make money. And the rhyme is not the only thing to link honeybees and internet host providers, who operate vast warehouses full of server computers on behalf of their customers. Sunil Nakrani of Oxford University and Craig Tovey of the Georgia Institute of Technology, in Atlanta, have recently developed what they believe is an efficient way of organizing internet servers, by mimicking the behavior of honeybee colonies. The unpredictability of internet traffic (sudden surges of shoppers or stockmarket trading) gives firms which run servers quite a headache. To see whether their analogy is useful, Nakrani and Tovey tested the honeybee algorithm against the so-called greedy algorithm currently used as the basis for the allocation of servers by most internet host providers. When internet traffic was highly variable, the honeybee algorithm outperformed greedy by as much as 20 percent.